PENGARUH PENGGUNAAN LKPD BERBASIS GROUP INVESTIGATION BERBANTUAN MIND MAP TERHADAP PENCAPAIAN KOMPETENSI IPA PESERTA DIDIK KELAS VIII SMPN 31 PADANG - Nurhabibah Nasution; Ratnawulan Ratnawulan; Hamdi Rifai (Universitas Negeri Padang, 2017)
There is a tendency for students to gain lack of competences. One of the factors is the minimum sources for students to study on the demand of 2013 curriculum. Therefore LKPD based on GI with mind map method is created in order to motivate students to be active in improving their competences. This study aims to investigate the differences and effects of LKPD based on GI with mind map method towards the competences of science class students of VIII SMPN 31 Padang in the aspects of knowledge, attitude, and skill. This was a quasi experiment research with randomized control group only design. The population were all of the students of VIII SMPN 31 Padang in the academic year of 2016/2017. This research used purposive sampling. Class VIII 6 was the experiment class while class VIII 7 was the control class. Data of the study included the competences of knowledge, attitude, and skill. Instruments of the study were a final test of knowledge competence, observation sheet of attitude competence, and scoring rubic of skill competence. T test was used to analyze the differences of students’ competences, linear regression was used to analyze the effects, and correlation test with r 0.5 for all competences. At the end of the study, it was an urgent to find out one of the ways to improve the students’ competences of knowledge, attitude, and skill.